Presence of Toxocara spp. in Domestic Cats in the State of Mexico - Gallegos, Lucila Marilú Rodríguez; Núñez, Camilo Romero; Gómez, Linda Guiliana Bautista; Castañeda, José Simón Martínez; Cardenas, Rafael Heredia (Acta Scientiae Veterinariae, 2016)
Background: Toxocara spp. is a gastrointestinal nematode with cosmopolitan distribution and is the most common parasite in domestic cats, which can deposit fertilized eggs in the environment with feces. Egg maturation starts in the soil, concluding two to three weeks after cat defecation, but eggs can remain viable in the soil for years and spread onto vegetables and into water. Infection of cats and paratenic hosts (among them humans) occurs through ingestion of infected eggs from the environment, through ingestion of paratenic hosts and, in puppies, through milk from infected mothers. The objective of the present study was to evaluate the presence of Toxocara spp. in domestic cats. Materials Methods & Results: In this study, 229 fecal samples from domestic cats were collected in the state of Mexico, Mexico. All of cats had an owner, and fresh feline feces were collected in previously labeled sterile bottles. Coproparasitological examinations were performed on these samples using a flotation technique with sodium hydroxide (NaOH) and sodium nitrate (NaNO3), Toxocara spp. eggs were identified under the microscope, in accordance with the morphological descriptions. The data were analyzed by means of Fisher’s exact test in order to compare the presence of Toxocara eggs according to cat age and sex. The chi-square test was used to determine associations between variables and odds ratios (OR) were calculated to determine the risk factors. Presence of Toxocara spp. eggs was identified in 42% (96/229) of the cats, of which 23% were males and 19% females. We did find an association between cats under the age of six months (P = 0.01) and the presence of Toxocara spp. eggs, and therefore age was determined to be a risk factor (OR = 1.69) for the presence of Toxocara spp. eggs in feces, cats over one year old showed a statistically significant association (P = 0.02) with the presence of parasite eggs in feces. The presence of Toxocara spp. was found to be a risk factor (OR = 1.57) among male cats aged less than 6 months, while among female cats a statistically significant association was found (P = 0.03) for the presence of Toxocara spp. Meanwhile, comparing positive cats of both sexes with age, a statistically significant difference (P = 0.02) was found regarding cats over one year old. Discussion: It were identified Toxocara spp. eggs in 42% of the feces of domestic cats from the state of Mexico. These results are similar to those reported by other studies in Mexico City, they also reported that there was a larger number of infected cats under one year of age and that males had higher infection rates. Comparison of both sexes with age showed a statistically significant association (P = 0.01) between cats under six months old and the presence of Toxocara eggs in feces. This age was also considered to be a risk factor (OR = 1.69) for parasite eggs in feces, during the first months of life, the larvae migrate and finish their cycle, but when the cat has reached its mature stage, the larvae may become entrenched and avoid finishing their life cycle. Male sex was identified as a risk factor for the presence of Toxocara spp. The prevalence of Toxocara spp. in domestic cats in the state of Mexico is high, and represents a potential risk of human toxocariasis. From the results found, it can be considered that cats are a major source of dissemination of environmental pollution and Toxocara spp.